Peran media sosial dalam melestarikan budaya tari topeng malangan - Alwi, Muhammad (Maliki Interdisciplinary Journal, 2025)
Malangan Mask Dance is a traditional performing art that originates from Malang, East Java, rich in cultural and historical values. However, this art faces serious challenges due to globalization and modernization, which have changed the interests of the younger generation. The preservation of Malangan Mask Dance is crucial for maintaining local cultural identity, and social media has emerged as an effective tool in this effort. Through platforms like Instagram, Facebook, and YouTube, information about Malangan Mask Dance can be disseminated quickly, including educational content that explains the meaning and techniques of the dance. The involvement of the younger generation is key to the preservation of this art, where social media can encourage active participation through campaigns and collaborations. The formation of communities on social media allows art enthusiasts to support each other and share information, raising awareness of the importance of local culture. However, challenges such as the spread of inaccurate information and changing interests of the younger generation towards modern content remain obstacles. Therefore, it is essential to ensure that the information disseminated is accurate and relevant, as well as to develop strategies that engage the younger generation so they remain connected to this valuable cultural heritage.